Development of Interactive Multimedia Assisted by Augmented Reality for Human Hearing Sense Material - Khusnunnisa', Mufida; Andriani , Aldina Eka (Journal of Educational Sciences, 2025)
This study aims to describe the development design, test the feasibility and effectiveness of Interactive Multimedia Assisted by Augmented Reality to improve learning outcomes of human hearing sense material for fourth-grade students at SD Negeri Pedurungan Tengah 02 Semarang. The type of research used is Research and Development (R&D) with a 4D model, which includes: define, design, develop, and disseminate. Data collection used tests (pre-test and post-test) and non-tests (observation, interviews, questionnaires, and documentation). The development design of Interactive Multimedia assisted by Augmented Reality used Canva as an interactive media presentation and Assemblr EDU as Augmented Reality visualization. The feasibility results from expert validation showed that the developed media was very feasible to use, with material validity of 93.4% and media validity of 95.3%. The effectiveness results showed a significant increase in student learning outcomes, with an average pretest score of 41.3 increasing to an average posttest score of 84.9, and an N-Gain of 0.76 with a high category. This study concludes that Interactive Multimedia assisted by Augmented Reality has been successfully developed, is highly feasible and effective in improving the learning outcomes of IPAS material on human hearing sense for fourth-grade students at SD Negeri Pedurungan Tengah 02 Semarang.